The Role of Law Enforcement Investigators in Addressing Sexual Violence under the Sexual Violence Crime Law (UU TPKS): A Case Study of Gerung Police Department, West Lombok - Islam, Rudi; Kusuma, Arbi; Fikri, Abdillah (Justicia Insight, 2025)
Law enforcement against sexual violence is a crucial aspect of state responsibility in protecting human rights, particularly the rights of victims. Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS) provides a more comprehensive legal framework for law enforcement officers, especially investigators, in handling sexual violence cases. This study aims to analyze the role of investigators in the enforcement of sexual violence laws within the jurisdiction of the Gerung Police Department, West Lombok. The research employs an empirical juridical approach with data collected through interviews, observations, and document studies. The findings reveal that investigators play a central role in the criminal investigation process, including receiving reports, gathering evidence, examining witnesses and victims, and submitting case files to the prosecutor's office. However, in practice, investigators face several challenges such as limited resources, lack of psychological support for victims, and prevailing socio-cultural pressures that often stigmatize victims. The UU TPKS serves as an essential guideline to strengthen the role of investigators, particularly in implementing a victim-centered approach that emphasizes the protection and restoration of victims' rights. Continuous training for investigators and cross-sectoral collaboration are needed to ensure the effective implementation of the UU TPKS at the regional level.